Financiación y demanda de educación superior estudio del caso en Colombia (1990-2005) (2008)
This document studies the statistical relationship between public and private ﬁnancing and the demand for higher education in Colombia. In particular, it addresses the three main cities in Colombia during 1990-2005. Through a panel data estimation, this study ﬁnds that increases in the average interest rate on education loans have a signiﬁcant impact on the number of students registered (or “university enrollment”) at higher education institutions. On the other hand, increases in wages for individuals that have attained higher education (namely, undergraduate or graduate degrees at colleges and/or universities) have a positive impact on the demand for higher education.